South America Climate During the 1970–2001 Pacific Decadal Oscillation Phases Based on Different Reanalysis Datasets - Silva, Maria Elisa Siqueira; Silva, Carlos Batista; Ambrizzi, Tercio; Drumond, Anita; Patucci, Natália Nunes (Frontiers in Earth Science, 2020)
In this paper, circulation and precipitation climate patterns over the South American domain obtained from NCEP-NCAR reanalysis I, JRA-55, and ERA-40 reanalysis datasets were intercompared within the period 1970–2001 in order to verify their climatic association with the Pacific Decadal Oscillation, PDO. Although all three datasets showed similar climatic patterns during each PDO phase, they showed distinct intensities for circulation and precipitation variables. The mean low frequency flow propagation over the South Pacific during negative and positive PDO phases reached central-eastern South America with opposite signals, contributing to the modulation of the local climate. During the negative PDO phases, the northerly flow over South America is intensified, while during the positive phase it is weakened. NCEP-NCAR reanalysis I, in comparison with JRA-55 and ERA-40 values, always indicates the strongest signal for circulation and precipitation variables. NCEP-NCAR reanalysis I meridional wind at the low-level jet area was about 5 and 12% larger than the respective JRA-55 and the ERA-40 values. For the positive and negative PDO phases, only NCEP-NCAR and ERA-40 high-level zonal wind anomalies showed divergent (positive PDO) and convergent (negative PDO) patterns close to 140° W at equatorial latitudes of the Pacific Ocean, respectively. This one indicated distinct representations of the positioning of Walker cells in the three reanalysis datasets. GPCC dataset, NCEP-NCAR, JRA-55, and ERA-40 reanalysis showed, in general, the dipole precipitation pattern over eastern South America, with signs of changes between the central-eastern and southeastern areas during PDO reversal phases. Over the central-eastern South American region, NCEP-NCAR precipitation is, on average, 57% larger than GPCC values, and 35 and 46% larger than JRA-55 and ERA-40 values, respectively. The observed patterns of anomalies for different PDO phases appeared in all reanalysis datasets, leading us to conclude that the physical meaning is independent from the datasets. Even considering the JRA-55 climate signal over South America associated with the PDO influence as the weakest one, the ability of JRA-55 to calculate monthly precipitation provided the highest linear correlation coefficient values in tropical areas, leading us to consider this dataset as the most reliable for the studied area.